1996
DOI: 10.1256/smsqj.53001
|View full text |Cite
|
Sign up to set email alerts
|

Variational retrieval of humidity profile, wind speed and cloud liquid-water path with the SSM/I: Potential for numerical weather prediction

Abstract: SUMMARYSeveral regression algorithms have been proposed to retrieve geophysical parameters from the Special Sensor Microwaveflmager (SSMfl) radiances. Their performances are generally limited by a simplified handling of nonlinearities and/or by the poor quality of the a priori information. In this paper, a variational method is proposed for retrieving the atmospheric humidity profile, the wind speed and the cloud liquid-water path from SSM/I observations over ocean. This method is based on nonlinear optimal es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 0 publications
1
36
0
Order By: Relevance
“…Results indicate that assimilation of SSM/I data with high horizontal resolution improved the horizontal distribution of the assimilated humidity. This agrees with the reports in recent papers (Filiberti et al, 1994;Phalippou, 1996). The results also suggest that this humidity adjustment leads to the improvement in large-scale precipitation forecasts as well as humidity forecasts over 48 hours.…”
Section: Direct Assimilationsupporting
confidence: 92%
See 2 more Smart Citations
“…Results indicate that assimilation of SSM/I data with high horizontal resolution improved the horizontal distribution of the assimilated humidity. This agrees with the reports in recent papers (Filiberti et al, 1994;Phalippou, 1996). The results also suggest that this humidity adjustment leads to the improvement in large-scale precipitation forecasts as well as humidity forecasts over 48 hours.…”
Section: Direct Assimilationsupporting
confidence: 92%
“…Retrieving these variables from TB's requires combining multichannel TB's. The relationship between TB's and the physical variables is nonlinear, as Phalippou (1996) pointed out. To linearize this relation, many retrieval algorithns use TB's calculated from the first guess of atmospheric and surface situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method has also proven to be successful in an early implementation of clear-sky infrared radiance assimilation in the past (e.g. Eyre et al, 1993;Phalippou, 1996) and for SSM/I brightness temperatures in clear-sky areas (GĂ©rard and Saunders, 1999). The application of the 1D + 4D-Var technique to assimilate observations from the Tropical Rainfall Measuring Mission (TRMM) precipitation radar by Benedetti et al (2006) has shown that active sensor data can provide useful information on the moisture field, but the results depend on the product types (level 1 versus level 2) and their underlying assumptions.…”
Section: Introductionmentioning
confidence: 99%
“…Now it is also available from the present operational US satellites National Oceanic and Atmospheric Administration (NOAA) F13, F14, F15 and IRS-P4/MSMR. Numerous studies have been carried out using these data from SSM/I in relation to the numerical model outputs (Liu et al, 1992;Phalippou, 1996;Ferraro, et al, 1996;Kar et al, 2003). These studies bring out the usability of such data by the NWP community in general.…”
Section: Introductionmentioning
confidence: 99%